2001
DOI: 10.1161/hc2901.093115
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Paternal History of Myocardial Infarction and Risk of Cardiovascular Disease in Men and Women

Abstract: Background-Few studies have examined the effects of paternal and maternal history of myocardial infarction (MI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
127
3
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(148 citation statements)
references
References 24 publications
10
127
3
8
Order By: Relevance
“…[1][2][3][4] The mechanisms underlying this familial clustering have not been firmly established but may include an increased susceptibility to atherosclerosis, 5 an increased tendency for thrombosis, 6 and proinflammatory responses suggested by high levels of C-reactive protein. 7 Wang et al 8 recently demonstrated a higher burden of subclinical atherosclerosis as assessed by carotid intimal thickness (IMT) in individuals with a parental history of premature CHD.…”
mentioning
confidence: 99%
“…[1][2][3][4] The mechanisms underlying this familial clustering have not been firmly established but may include an increased susceptibility to atherosclerosis, 5 an increased tendency for thrombosis, 6 and proinflammatory responses suggested by high levels of C-reactive protein. 7 Wang et al 8 recently demonstrated a higher burden of subclinical atherosclerosis as assessed by carotid intimal thickness (IMT) in individuals with a parental history of premature CHD.…”
mentioning
confidence: 99%
“…Varios estudios previos han demostrado la relación que existe entre el peso de los individuos al nacer y su riesgo de desarrollar enfermedad coronaria, hipertensión y diabetes en el futuro. Barker et al han propuesto que la adaptación fetal a una nutrición intrauterina inadecuada, debida a insuficiencia placentaria, resulta en la programación de un "fenotipo ahorrador" que permite a los individuos sobrevivir en condiciones de carencia nutricional, pero, una vez estas son superadas y se logra una nutrición adecuada, se incrementa el riesgo de enfermedad coronaria e hipertensión arterial (34). El bajo peso puede explicarse por un parto prematuro o por restricción del crecimiento intrauterino.…”
Section: Discussionunclassified
“…5 In multiple prospective studies involving hundreds of thousands of men and women, a parental history of premature CHD is a significant risk factor for CVD even after multivariable adjustment. Relative risk estimates generally range from 1.2 to 2.0, as noted in the Physician's Health Study and Women's Health Study, 6 although the estimated magnitude of risk associated with early-onset parental disease is substantially higher in some studies. 7 However, what has remained unclear are the pathophysiological/genetic mechanisms of the familial risk, the extent to which familial risk is independent of other established risk factors (including hyperlipidemia, hypertension, and tobacco use, which have a familial component), the magnitude of excess risk after adjustment for other risk factors, and the extent to which risk conferred by a positive family history of CHD is modifiable.…”
Section: See P 2150mentioning
confidence: 96%